2018
DOI: 10.14202/vetworld.2018.1349-1356
|View full text |Cite
|
Sign up to set email alerts
|

Effects of secretome on cisplatin-induced testicular dysfunction in rats

Abstract: Background:Testicular dysfunction is a degenerative disorder characterized by failure in the synthesis of reproductive hormones and spermatogenesis. Secretome derived from the human umbilical mesenchymal stem cell (MSC) has been reported to repair some degenerative disorders.Aim:This study aimed to investigate the effect of secretome derived from the human umbilical MSCs on cisplatin-induced testicular dysfunction in rats.Materials and Methods:Thirty-six male Wistar rats were divided into the control and secre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Spermatogenesis regeneration was proved by increasing the sperm number and motility. Also, there was improvement in the structure of seminiferous tubules [ 16 ]. However, the presence of cytokines, especially IL-6 and IL-10, in the regeneration of testicular dysfunction rat treated with secretome has not been studied yet.…”
Section: Introductionmentioning
confidence: 99%
“…Spermatogenesis regeneration was proved by increasing the sperm number and motility. Also, there was improvement in the structure of seminiferous tubules [ 16 ]. However, the presence of cytokines, especially IL-6 and IL-10, in the regeneration of testicular dysfunction rat treated with secretome has not been studied yet.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the most significant result was noted with CM collected after 24 hours of incubation, in comparison to 48 and 72 hours, with comparable results noted in both stressed and non-stressed sperm. In line with these results, a study conducted by Prihatno et al (26) showed that high-dose secretome derived from the human fetal umbilical cord was able to increase the number and motility of sperm cells in rats with cisplatin-induced testicular dysfunction, and to promote the regeneration of the seminiferous tubules. On the other hand, Mokarizadeh et al (27) revealed that stem cells secretome can improve viability, motility and antioxidant capacity parameters of cryopreserved adult male Wistar rats sperm.…”
Section: Discussionmentioning
confidence: 59%
“…The P1 and P2 groups were injected with cisplatin to induce testicular dysfunction, and continued with an injection dose of 0.2 ml/kg BW and 0.5 ml/kg BW of mesenchymal stem cells-conditioned medium. The rats in the treated groups were injected with Cisplatin (PT Dankos Farma, Kalbe Company, Indonesia) at a dose of three mg/kg BW three times at three-day intervals (Reddy et al, 2016;Prihatno et al, 2018). The mesenchymal stem cells-conditioned medium was injected one time a week for four times after all doses of cisplatin were injected.…”
Section: Experimental Animalsmentioning
confidence: 99%